Research Data Handling by Researchers in the Selected Universities in Tanzania - Buhomoli, Obadia Shadrack; Muneja, Paul S (University of Dar es Salaam Library Journal, 2022)
This study investigated the practice of research data handling in the selected higher learning institutions in Tanzania, with specific reference to the University of Dar es Salaam and University of Dodoma. The study assessed research data formats that are currently produced, where the research data are currently stored and whether researchers in the selected institutions use data management plan in their research activities. A study used both quantitative and qualitative approaches. Questionnaire was used to extract data from researchers while interview was used to obtain data from key informants who were categorized as potential managers responsible for research data management from the respective institutions. Results show that researchers have been producing various kinds of research data in various formats both digital and analogy data. Moreover, researchers handled these data using various approaches. This means that there were no systematic and well-guided methods of handling their research data making the data prone to get lost. Only a small number of researchers appeared to have a large amount of research data. Furthermore, only a few number of researchers indicated to have used research data management plan (RDM) in their research activities. This study recommends more collaboration among researchers, directorate of research and publication, ICT and library management to improve the research data handling in the universities.